If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 15) = 17x Reorder the terms: 4(15 + x) = 17x (15 * 4 + x * 4) = 17x (60 + 4x) = 17x Solving 60 + 4x = 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. 60 + 4x + -17x = 17x + -17x Combine like terms: 4x + -17x = -13x 60 + -13x = 17x + -17x Combine like terms: 17x + -17x = 0 60 + -13x = 0 Add '-60' to each side of the equation. 60 + -60 + -13x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -13x = 0 + -60 -13x = 0 + -60 Combine like terms: 0 + -60 = -60 -13x = -60 Divide each side by '-13'. x = 4.615384615 Simplifying x = 4.615384615
| -4y+8=5y+9 | | -4(-2+5)= | | 5t^2+14x+3=0 | | 6y+8y=98 | | 15+2(9-6)+9= | | 5x-y+15=0 | | 15+2(9-6)-9= | | x-15=-4 | | -18+12+-6= | | -9(3b+1)+(28b-9)=0 | | (-18)(12)(-6)= | | 5p-6(p-5)+5(q-5)= | | 3(-6)(4)(-2)= | | (6u^3)(-5u^7v^6)= | | 3(-6)(4)(-2)=(-18)(12)(-6) | | 18=6x | | 9y-7(x-y)-x= | | N^2-3+2=0 | | 13x+6-3=12x-3 | | 4(9b+c-5a)-5(a-3c+4b)= | | 33=(3x-8)(7x+4) | | 7(p+7q-13)= | | N^2-13n+40=0 | | 5(6y+12)=6(12y-4) | | 30=-1.2v | | 2x^2+10x-18=0 | | 5(6y+12)=6(12-4) | | -2(4n+4)=2 | | 15x^4-12x^3+3x^2=0 | | y-(-3)=2(x-2) | | (-1)x^3=27 | | 6x+2.72=4.22 |